3, 3-Difluoro-3, 4, 5, 6-tetrahydropyridin-2-amines: Potent and permeable BACE-1 inhibitors. Issue 8 (15th April 2020) - Peschiulli, Aldo; Oehlrich, Daniel; Rombouts, Frederik; Vos, Ann; Gijsen, Harrie JM
Graphical abstract: Abstract: Since its discovery in 1999, BACE-1, a membrane anchored aspartyl protease expressed primarily in the CNS, has been the target of numerous medicinal chemistry research programs. These efforts have produced highly potent inhibitors with nanomolar affinity and ever-increasing structural complexity. However, only a handful of these molecules have been able to combine in vitro potency with CNS permeability and progressed to the clinic. Herein, we describe a set of novel piperidine-based inhibitors. This investigation culminated with the identification of 43, a highly potent (IC50 : 1.5 nM), permeable BACE-1 inhibitor with a low susceptibility to Pgp-mediated efflux.